KEDUDUKAN BUKTI ELEKTRONIK DALAM PEMBUKTIAN PERKARA PERCERAIAN - Susylawati, Eka (STAIN PAMEKASAN, 2015)
To prove is to convince the judge about the truth of argumentation or occasion that has been argued by all sides in a legal action in court. Based on the Article 164 HIR/Article 284 RBg and Article 1866 KUH Perdata, it has been stated the five evidences of civil case in Indonesia, they are letter evidence, witness evidence, presumption, confession, and oath. In the current progress, electronics devices are the needs and become something ordinary when data or anything produced by the electronic devices converted to be valid evidences of any events and occasions. In the case of divorce, a husband or/and wife occasionallyÂ Â submits electronic evidences in a court such as photos, SMS (short message service), recorded voice or picture (video) to support the argumentation of affair committed by a couple.Â